Increased BNIP3-mediated mitophagy attenuates GDAP1 loss of function - implications for Charcot-Marie-Tooth disease 4A. - Zhang, L.; Pouya, A.; Kopetzky, J.; Bitar, S.; Wolf, C.; Bello, F.D.; Gomez-Zepeda, D.; Tenzer, S.; Methner, A. (Neurobiology of Disease, 2025)
Charcot-Marie-Tooth disease type 4 A ((CMT4A), an autosomal recessive neuropathy, is caused by mutations in ganglioside-induced differentiation-associated protein 1 (GDAP1). GDAP1 resides in the outer mitochondrial membrane facing the cytosol and is involved in mitochondrial dynamics and function. Its perturbation affects mitochondrial shape, contact sites, redox homeostasis and cellular metabolism. In response to GDAP1 knockdown in a human neuronal cell line, we found increased mitochondrial turnover, biogenesis and mitophagy. This was associated with more lysosomal proteins in mitochondrial fractions including BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3) and its homolog BNIP3-like (BNIP3L) - proteins involved in the recruitment of autophagy machinery via direct interaction. Flies with neural Gdap1 knockdown also exhibited upregulated levels of the sole BNIP3 ortholog. Neural expression of human BNIP3 reduced the detrimental effects of Gdap1 knockdown on eclosion and climbing ability in adult flies, while simultaneous knockdown of both genes was detrimental. These findings suggest that increased BNIP3-driven mitophagy may act as a protective mechanism, partially counteracting the cellular dysfunction caused by GDAP1 loss of function, and highlight the potential of targeting mitophagy pathways as a therapeutic strategy for CMT4A.